Platelet-rich plasma - a revolutionary therapeutic option in multi-disciplinary indications - Kiełkowicz, Aleksandra; Pisera, Piotr; Pactwa, Filip; Popińska, Zuzanna; Żmuda, Bartłomiej; Ślusarczyk, Daniel; Jakubowska, Wiktoria; Żuberek, Michał (Journal of Education, Health and Sport, 2024)
Background: Platelet-rich plasma (PRP) was originally described as a small volume of plasma that contains higher concentrations of platelets, compared to peripheral blood. Although currently the use of PRP in most indications is off-label, it is not prohibited. Initially, PRP was used for wound healing and tissue regeneration in fields such as orthopaedics, dermatology, maxillofacial surgery and dentistry. Aim of the study: The aim of this article was to present and summarise the modern production methods, the mechanism of action at the molecular and biochemical level and the most important uses and indications of PRP in present-day medicine. Material and methods: A cross-sectional search of relevant literature was performed in databases using accepted wording. Publications from 2003-2023 were included. The entire process has been supplemented with additional procedures to increase the reliability of this publication. Results: Orthopaedics has gained many minimally invasive therapeutic solutions thanks to PRP. Its effects on ligament and tendon tissues have been studied, where promising data have been proven. Also in aesthetic medicine and dermatology, many treatment strategies have been developed using PRP, mainly for the treatment of acne, androgenic alopecia and delaying tissue ageing as much as possible. Conclusion: Platelet-rich plasma has found application in the treatment of many conditions in orthopaedics, dermatology, aesthetic medicine and dentistry. It is characterised by good therapeutic efficacy, with relatively low risk. However, high-quality studies are still lacking to provide more reliable data.